Re-using manuscripts in late Medieval England repairing, recycling, sharing - Ryley, Hannah 1990- (York Medieval Press, 2022)
A fresh appraisal of late medieval manuscript culture in England, examining the ways in which people sustained older books, exploring the practices and processes by which manuscripts were crafted, mended, protected, marked, gifted and shared
Title from publisher's bibliographic system (viewed on 22 Jul 2022)
Keywords: Geschichte 1374-1500; Manuscripts, Medieval / England; Manuscripts / Conservation and restoration / England / History / To 1500; Book industries and trade / England / History / To 1500; Early printed books / England; Handschrift; Makulatur; Wiederverwendung; England